Adoption of technology perspectives from the LEADX : leadership & the how to's of digital transformation - Salipsip, Demetrio Jr., P. (Enderun Colleges Scholarly Review, 2020)
This exploratory study focuses on the technological adoption category traits of the participants based on Rogers Adoptive Categories: innovators, early adapters, early majority, late majority, and laggards. Ninety one percent (91%) of surveyed participants are millennials, thus, the result based on the findings confirmed that millennials tend to be innovators and early adopters. Results show also that peers and family are the greatest influence on the participants' decision to adopt technology while they are reluctant to do so because of cost implementation.